Integration of Direct Instruction Methods and Independent Learning Curriculum in the Teacher Training and Development Program (TTDP) at Darussalam Gontor University - Moh. Alwi Yusron; Saiful Anwar; Halida Umami; Muhammad Haikal; Idam Mustofa (Educan, 2024)
This research investigates the implementation of the Integration of Direct Instruction Methods and Independent Learning Curriculum in the Teacher Training and Development Program (TTDP) at Darussalam Gontor University. The study employs a case study method to delve into the understanding of the execution, strengths, weaknesses, challenges, and opportunities within this integration. Findings reveal that TTDP at Darussalam Gontor University follows a three-step process: planning, execution, and evaluation. The execution involves the delivery of basic TTDP content, practical activities, and evaluation through tests and learning observations. The strengths of this integration lie in the enhancement of teaching quality, enabling trainee teachers to design more engaging learning experiences. However, challenges surface in the form of initial resistance to a shift in teaching paradigms and the need for institutional support. Opportunities exist in developing the professionalism of aspiring teachers and creating dynamic teaching materials. This research provides in-depth insights into the TTDP implementation, highlighting both positive changes and obstacles that need to be addressed. It contributes to understanding how the integration of direct instruction methods and independent learning curriculum can improve teacher training within this university context.